Joint commissioning in health and social care: An exploration of definitions, processes, services and outcomes - Dickinson, H.; Glasby, J.; Nicholds, A.; Jeffares, S.; Robinson, Suzanne; Sullivan, H. (National Institute for Health Research, Service Delivery and Organisation Programme, 2013)
Despite government suggestions that joint commissioning between health and social care is (or at least should be) a key element of attempts to improve the health and well-being of local populations, the evidence to support this notion has lagged behind this aspiration. Although there is a wealth of different partnership arrangements in place around the country, there are a number of limitations to our existing knowledge relating to how these operate in practice and the types of impacts that these produce. Underpinning this study is a desire to explore a working hypothesis common in current policy and practice: that partnerships lead to better services and hence better outcomes for service users and their carers .Thus, this research seeks to investigate whether joint commissioning leads to improved services and subsequently improved outcomes for service users. To test this link in greater detail, this research seeks to provide a theoretically and empirically robust understanding of the dynamic relationship between joint commissioning, services and outcomes. Eight case study sites will be incorporated into this research, representing a range of the different types of commissioning activities which are in place around the country. This research project seeks to add to and complement existing and future SDO and Department of Health research projects to produce more clarity in relation to the types of activities and outcomes which joint commissioning is producing around England and make generalisable statements relating to what works for whom and within what circumstances' (Pawson and Tilley, 1997).